Influence of catchment vegetation on mercury accumulation in lake sediments from a long-term perspective - Rydberg, Johan; Rösch, Manfred; Heinz, Emanuel; Biester, Harald (The science of the total environment, 2015)
Organic matter (OM) cycling has a large impact on the cycling of mercury (Hg) in the environment. Hence, it is important to have a thorough understanding on how changes in, e.g., catchment vegetation - through its effect on OM cycling - affect the behavior of Hg. To test whether shifts in vegetation had an effect on Hg-transport to lakes we investigated a sediment record from Herrenwieser See (Southern Germany). This lake has a well-defined Holocene vegetation history: at ~8700years BP Corylus avellana (hazel) was replaced by Quercus robur (oak), which was replaced by Abies alba (fir) and Fagus sylvatica (beech) ~5700years BP). We were particularly interested in testing if coniferous vegetation leads to a larger export of Hg to aquatic systems than deciduous vegetation. When hazel was replaced by oak, reduced soil erosion and increased transport of DOM-bound mercury from the catchment resulted in increases in both Hg-concentrations and accumulation rates (61ngg−1 and 5.5ngcm−2yr.−1 to 118ngg−1 and 8.5ngcm−2yr.−1). However, even if Hg-concentrations increased also in association with the introduction of fir and beech (173ngg−1), as a result of higher Hg:C, there was no increase in Hg-accumulation rates (7.6ngcm−2yr.−1), because of a decreased input of OM. At around 2500years BP Hg-accumulation rates and Hg-concentration indicated an additional input of Hg to the sediment (316ngg−1 and 10.3ngcm−2yr.−1), which might be due to increased human activities in the area, e.g., forest burning or mining. Our results contrast those of several paired-catchment studies that suggest a higher release of Hg from coniferous than deciduous forest, and there is a need for studies with a long-term perspective to increase our understanding of the effects of slow and gradual processes on mercury cycling.
Gesehen am 30.10.2019